2014
DOI: 10.1016/j.ijindorg.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Does innovation stimulate employment? A firm-level analysis using comparable micro-data from four European countries

Abstract: This paper studies the impact of process and product innovations introduced by firms on employment growth in these firms. A simple model that relates employment growth to process innovations and to the growth of sales separately due to innovative and unchanged products is developed and estimated using comparable firm-level data from France, Germany, Spain and the UK. Results show that displacement effects induced by productivity growth in the production of old products are large, while those associated with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
369
4
40

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(474 citation statements)
references
References 34 publications
23
369
4
40
Order By: Relevance
“…This finding confirms the visual story in the funnel plots – and is consistent with the suspicion that some researchers report selectively those empirical results that are statistically significant in the ‘right’ direction. In other words, there is a preponderance of confirmatory estimates that support the theoretical predictions process innovation has a negative effect on employment, whereas product innovation has a positive effect (Katsoulacos, ; Harrison et al ., , ) . This finding demonstrates that the theory congruent conclusions reported in narrative reviews may be misleading as they are based on highly selected evidence.…”
Section: Hierarchical Meta‐regression Resultsmentioning
confidence: 99%
“…This finding confirms the visual story in the funnel plots – and is consistent with the suspicion that some researchers report selectively those empirical results that are statistically significant in the ‘right’ direction. In other words, there is a preponderance of confirmatory estimates that support the theoretical predictions process innovation has a negative effect on employment, whereas product innovation has a positive effect (Katsoulacos, ; Harrison et al ., , ) . This finding demonstrates that the theory congruent conclusions reported in narrative reviews may be misleading as they are based on highly selected evidence.…”
Section: Hierarchical Meta‐regression Resultsmentioning
confidence: 99%
“…Using CIS data from four European countries (France, Germany, Spain, and UK), Harrison et al [11] showed that process innovation was responsible for employment displacement (although compensation mechanisms were at work), while product innovation was fundamentally labor-friendly.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…stimulate a new demand for products and, in turn, additional production and employment ( [31][32][33] chaps. 11, [11,12,[34][35][36]). However, there are three drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…This trade-off was first put forward by David Ricardo in his chapter ''On Machinery'' 2 and was later modelled by Smolny (1998). It has motivated a thorough analysis of the differentiated impact of product versus process innovations on employment by Harrison et al (2014) (on data from France, Germany, Spain and the UK) and Hall et al (2008) (on Italian data). Using slightly different methodologies, both studies disagree on the existence of a displacement effect of process innovations, but converge on a positive impact from the commercialization of new products.…”
Section: Theoretical Roots and Previous Empirical Evidencementioning
confidence: 99%
“…Due to the trade-off between the labour-saving and labour-creating effects of innovation (Smolny 1998;Harrison et al 2014;Hall et al 2008), the net impact of R&D expenditure on employment growth is ambiguous. If we implicitly assume an ideal pattern linking, unidirectionally, R&D to innovation to productivity to employment growth (where direct intermediate steps linking nonadjacent rings of this chain are also possible), our study will take into account only the first and the last rings of this chain, such information integrating the probability that the innovation process would fail.…”
Section: Introductionmentioning
confidence: 99%